LOFAR reveals the giant: a low-frequency radio continuum study of the outflow in the nearby FR I radio galaxy 3C 31. Issue 4 (10th November 2017) - Heesen, V; Croston, J H; Morganti, R; Hardcastle, M J; Stewart, A J; Best, P N; Broderick, J W; Brüggen, M; Brunetti, G; Chyży, K T; Harwood, J J; Haverkorn, M; et al.
Abstract: We present a deep, low-frequency radio continuum study of the nearby Fanaroff–Riley class I (FR I ) radio galaxy 3C 31 using a combination of LOw Frequency ARray (LOFAR; 30–85 and 115–178 MHz), Very Large Array (VLA; 290–420 MHz), Westerbork Synthesis Radio Telescope (WSRT; 609 MHz) and Giant Metre Radio Telescope (GMRT; 615 MHz) observations. Our new LOFAR 145-MHz map shows that 3C 31 has a largest physical size of 1.1 Mpc in projection, which means 3C 31 now falls in the class of giant radio galaxies. We model the radio continuum intensities with advective cosmic ray transport, evolving the cosmic ray electron population and magnetic field strength in the tails as functions of distance to the nucleus. We find that if there is no in situ particle acceleration in the tails, then decelerating flows are required that depend on radius r as v ∝ r β (β ≈ −1). This then compensates for the strong adiabatic losses due to the lateral expansion of the tails. We are able to find self-consistent solutions in agreement with the entrainment model of Croston & Hardcastle, where the magnetic field provides ≈1/3 of the pressure needed for equilibrium with the surrounding intracluster medium. We obtain an advective time-scale of ≈190 Myr, which, if equated to the source age, would require an average expansion Mach number M ≈ 5 over the source lifetime. Dynamical arguments suggest that instead either the outer tail material does not represent the oldest jet plasma or else the particle ages are underestimated due to the effects of particle acceleration on large scales.